Onur İnal and Yavuz Köse (eds.), Seeds of Power: Explorations in Ottoman Environmental History - Vlachos, George L. (The Historical Review/La Revue Historique, 2023)
Review of Onur İnal and Yavuz Köse (eds.), Seeds of Power: Explorations in Ottoman 259 Environmental History